Unraveling the role of Breg cells in digestive tract cancer and infectious immunity - Moreira, Helena; Dobosz, Agnieszka; Cwynar-Zając, Łucja; Nowak, Paulina; Czyżewski, Marek; Barg, Marta; Reichert, Paweł; Królikowska, Aleksandra; Barg, Ewa (Frontiers in Immunology, 2022)
Over the past two decades, regulatory B cells (Breg cells or Bregs) have emerged as an immunosuppressive subset of B lymphocytes playing a key role in inflammation, infection, allergy, transplantation, and cancer. However, the involvement of Bregs in various pathological conditions of the gastrointestinal tract is not fully understood and is the subject of much recent research. In this review, we aimed to summarize the current state of knowledge about the origin, phenotype, and suppressive mechanisms of Bregs. The relationship between the host gut microbiota and the function of Bregs in the context of the disturbance of mucosal immune homeostasis is also discussed. Moreover, we focused our attention on the role of Bregs in certain diseases and pathological conditions related to the digestive tract, especially Helicobacter pylori infection, parasitic diseases (leishmaniasis and schistosomiasis), and gastrointestinal neoplasms. Increasing evidence points to a relationship between the presence and number of Bregs and the severity and progression of these pathologies. As the number of cases is increasing year by year, also among young people, it is extremely important to understand the role of these cells in the digestive tract.